Hubungan Antara Keaktifan Organisasi dengan Citra Diri pada Mahasiswa Universitas Islam Sultan Agung - Liffia Layyinatus Syifa’; Bettie Febriana; Wahyu Endang Setyowati (Journal of Medical Practice and Research, 2025)
Higher education institutions function not only as centers for the development of knowledge but also as platforms for shaping students’ character and personality. One important aspect of the learning process in universities is student involvement in campus organizations. Through these organizations, students have the opportunity to develop various personal potentials, such as leadership skills, time management, and communication abilities, all of which contribute to the formation of a positive self-image. This study addresses the importance of organizational involvement in the development of students’ self-image, particularly at Sultan Agung Islamic University, due to the limited number of studies examining this relationship in this context.This study uses a quantitative design with a cross-sectional approach. The sample consists of 130 students selected using purposive sampling. Data were collected using questionnaires that measured students’ organizational involvement and their self-image. The Spearman Rank test was used to analyze the data.The results show that 63.8% of students have a good level of organizational involvement, and 77.7% of respondents demonstrate a positive self-image. Statistical analysis indicates a p-value of < 0.001, signifying a significant relationship between organizational involvement and self-image. The correlation coefficient of 0.884 indicates a strong and positive relationship, meaning that the more active students are in organizational activities, the better their self-image tends to be.